HPV testing in first‐void urine provides sensitivity for CIN2+ detection comparable with a smear taken by a clinician or a brush‐based self‐sample: cross‐sectional data from a triage population. (20th July 2017) - Leeman, A; del Pino, M; Molijn, A; Rodriguez, A; Torné, A; de Koning, M; Ordi, J; van Kemenade, F; Jenkins, D; Quint, W
Abstract : Objective: To compare the sensitivity of high‐risk human papillomavirus (hrHPV) and genotype detection in self‐collected urine samples in the morning (U1), and later on (U2), brush‐based self‐samples (SS), and clinician‐taken smears (CTS) for detecting cervical intraepithelial neoplasia grade 2+ (CIN2+) in a colposcopic referral population. Design: Cross‐sectional single‐centre study. Setting: A colposcopy clinic in Spain. Population: A cohort of 113 women referred for colposcopy after an abnormal Pap smear. Methods: Women undergoing colposcopy with biopsy for abnormal Pap smears were sent a device (Colli‐Pee™, Novosanis, Wijnegem, Belgium) to collect U1 on the morning of colposcopy. U2, CTS, and SS (Evalyn brush™, Rovers Medical Devices B.V., Oss, the Netherlands) were also analysed. All samples were tested for HPV DNA using the analytically sensitive SPF10‐DEIA‐LiPA25 assay and the clinically validated GP5+/6+‐EIA‐LMNX. Main outcome measures: Histologically confirmed CIN2+ and hrHPV positivity for 14 high‐risk HPV types. Results: Samples from 91 patients were analysed. All CIN3 cases ( n = 6) tested positive for hrHPV in CTS, SS, U1, and U2 with both HPV assays. Sensitivity for CIN2+ with the SPF10 system was 100, 100, 95, and 100%, respectively. With the GP5+/6+ assay, sensitivity was 95% in all sample types. The sensitivities and specificities for both tests on each of the sample types did not significantly differ. There was 10–14% discordance on hrHPV genotype. Conclusions: CIN2+ detection using HPV testing of U1 shows a sensitivity similar to that of CTS or brush‐based SS, and is convenient. There was substantial to almost excellent agreement between all samples on genotype with both hrHPV assays. There was no advantage in testing U1 compared with U2 samples. Tweetable abstract: Similar CIN2+ sensitivity for HPV testing in first‐void urine, physician‐taken smear and brush‐based self‐sample. Tweetable abstract: Similar CIN2+ sensitivity for HPV testing in first‐void urine, physician‐taken smear and brush‐based self‐sample.